Future work now: the rise of remote work - Hennigan, Rowena (Henry Stewart Talks, 2020)
Business response to COVID-19 worldwide and in the US, Business continuity, Work from home before and after COVID-19, Areas covered by the series, Introduction of the series’ speakers